Pregnancy and weight monitoring: A feasibility study of weight charts and midwife support. Issue 4 (28th March 2020) - Sanders, Julia; Channon, Sue; Cannings‐John, Rebecca; Coulman, Elinor; Hunter, Billie; Paranjothy, Shantini; Warren, Lucie; Drew, Cheney; Phillips, Bethan
Abstract: Around half of pregnant women in the United Kingdom are overweight or obese. The antenatal period provides an opportunity for encouraging women to adopt positive lifestyle changes, and in recent years, this has included development of strategies to support women in avoiding excessive gestational weight gain. The objective of this interventional cohort study was to incorporate individualised gestational weight monitoring charts supported by motivational interviewing (MI)‐based conversations into midwifery‐led antenatal care and assess potential of the intervention for further development and evaluation. The study setting was a community midwifery team within a large maternity unit. The study explored the facilitators and barriers to engagement with the intervention as experienced by women and midwives; 52 women were recruited, of whom 48 were included in the analysis. A single training session was found adequate to prepare midwives to use antenatal weight charts but was insufficient to result in the incorporation of motivational interview techniques into clinical practice. We did not find sufficient evidence to recommend effectiveness testing of this intervention, and there is currently insufficient evidence to support reintroducing regular weighing of pregnant women into UK antenatal care. Given the public health importance of reducing rates of obesity, future interventions aimed at controlling gestational weight gain should continue to be developed but need to include innovative strategies particularly for women who are already obese or gain weight above that recommended.